INFORMAL LEARNING AND NONFORMAL EDUCATION IN RANTE LIMBONG COMMUNITY - Amir Patintingan; Elihami Elihami; Mustakim Mustakim; Nurisan Lateh (JURNAL EDUKASI NONFORMAL, 2019)
The purpose of this research is to revolutionize the mentality of the Lembang community / Rante Liombong Villagem motivate and stimulate the work spirit of the Lembang / Rante Liombong Village community and the character of the community must act for change in a better direction. The target of this study is to become a community of integrity, willing to work hard, and have a mutual cooperation spirit. ", The Lembang / Rante Limbong village are aware of effective and efficient work, passionate and motivated to improve work outcomes. The main problem is having a weak mentality that is consumptive always wanting to get something by the Instant way. Large land is not utilized as well as possible, it is left to be a land to sleep without any plants, people prefer lazing at home especially for young people, do not have work ethic, work as they wish, during alcoholic drinks, cockfighting every evening , card gambling all night, even though they need big funds for their party costs, especially the Rambu Solo party.The method used in the activities of the Science and Technology application for society (IbM) is Participatory Rural Appraisal (PRA), which involves the community in activities. The implementation of this activity is through Sikombong (Socialization), assistance, field study and demonstration and evaluation to see the effectiveness of the program so that the program runs effectively and efficiently. The implementation method is to apply and apply an active, effective and efficient work model in order to increase productive work outcomes.